Relationship between public entities that provide health care and the universities for the training of human talent in the area of Nutrition, experience of the School of Nutrition, University of Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2025)
This review of the topic describes the importance of the relationship between the University of Costa Rica and institutions that provide health services. It also details the teaching role of health professionals in the curricular formation of university nutrition students
Keywords: training of human talent in Nutrition; public entities in the training of human talent; hospital clinical quotas; clinical practices; hospital teachers